The prevalence of and risk factors for prostatitis‐like symptoms and its relation to erectile dysfunction in Chinese men. (November 2015) - Zhang, Z.; Li, Z.; Yu, Q.; Wu, C.; Lu, Z.; Zhu, F.; Zhang, H.; Liao, M.; Li, T.; Chen, W.; Xian, X.; Tan, A.; et al.
Summary: The aim of this study was to describe the prevalence of and risk factors for prostatitis‐like symptoms and its relation to erectile dysfunction (ED) among southern Chinese men. Data were collected from 2790 men attending the Fangchenggang Area Male Healthy and Examination Survey from September 2009 to December 2009. The prostatitis‐like symptoms were assessed by the NIH Chronic Prostatitis Symptom Index and ED was assessed using the 5‐item International Index of Erectile Function. Lifestyle and demographic characteristics were obtained through a questionnaire. Prevalence of prostatitis‐like symptoms was 12.4% among 2790 Chinese men aged 20–84 years. In smokers who smoked ≥20 cigarettes per day (age‐adjusted OR = 1.29; 95% CI = 1.00–1.66; p  =   0.04), physical inactivity (age‐adjusted OR = 1.31; 95% CI = 1.03–1.66; p  = 0.02) was a significant risk factor for prostatitis‐like symptoms. Alcohol consumption (daily drinking) also was a risk factor for prostatitis‐like symptoms, although the differences were not statistically significant (age‐adjusted OR = 1.36; 95% CI = 0.96–1.92; p  = 0.07). Those with diabetes may also be at higher risk for prostatitis‐like symptoms (age‐adjusted OR = 1.37; 95% CI = 0.85–2.21; p  = 0.19). In addition, men with ED were more likely to have had prostatitis‐like symptoms (age‐adjusted OR = 1.86; 95% CI = 0.47–2.36; p  < 0.0001), and the ORs increased with increasing severity of ED status (mild ED, mild to moderate ED, and moderate to severe ED were 1.57, 2.62, and 3.24, respectively. Test for trend, p  = 0.0001). Our results show that prostatitis‐like symptoms are prevalent in Southern China affecting men of all ages. Smoking, drinking, lack of physical activity, and elevated plasma glucose level were associated with an increased risk of prostatitis‐like symptoms. In addition, our results reveal that ED accounted for a large proportion (61.5%) among men with prostatitis‐like symptoms; we also confirm the magnitude of ED associated with prostatitis‐like symptoms. Thus, interventions to evaluate and improve ED might help ameliorate prostatitis‐like symptoms and vice versa.